2019
DOI: 10.1111/clr.13537
|View full text |Cite
|
Sign up to set email alerts
|

A preclinical model links osseo‐densification due to misfit and osseo‐destruction due to stress/strain

Abstract: Objective Primary stability is a prerequisite for implant osseointegration. Some degree of misfit between an implant and its osteotomy is required to ensure primary stability, and this is typically achieved by undersizing an implant osteotomy. In this preclinical study, we aimed at understanding the relationship between misfit, insertion torque, implant stability, and their cumulative short‐ and longer‐term effects on peri‐implant bone. Materials and methods We placed implants in maxillary extraction sites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…Because most of the studies on the osseodensification technique are not clinical, some reviews have shown the effectiveness of this method in improving primary stability in medullary bone [31,32]; however, it is still unclear whether secondary stability is positively or negatively affected by this surgical technique [3,33]. Further clinical studies are required to analyze how implant stability varies during the healing period subsequent to the two surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because most of the studies on the osseodensification technique are not clinical, some reviews have shown the effectiveness of this method in improving primary stability in medullary bone [31,32]; however, it is still unclear whether secondary stability is positively or negatively affected by this surgical technique [3,33]. Further clinical studies are required to analyze how implant stability varies during the healing period subsequent to the two surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recently a preclinical study analyzed misfit and osteodestruction due to stress/strain linked to the osseodensification technique [33]. One of the most common questions about the osseodensification protocol involves micro-fractures in the peri-implant bone that cause a huge zone of dying osteocytes [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a previous study we created a situation where an implant was placed into an undersized osteotomy. Inserting the implant produced compressive strains that severely damaged the peri‐implant bone, resulting in sustained resorption and implant loosening and ultimately, fibrous encapsulation (Coyac et al., 2019). Here, we created a situation where an implant was placed into an oversized osteotomy, and in this case, immediate loading of the implants was a key to their failure: loading generated high strains in the gap interface (Figure 1), resulting in an unfavorable environment for osteogenic cell differentiation (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to identify areas for potential improvement, we and other groups have studied the biomechanical features of osteotomy site preparation and implant placement. [1][2][3] The historical literature advises the careful preparation of an implant bed, followed by a healing period to allow the remodeling of bone damaged by drilling. 4 Even with copious irrigation, osteotomy site preparation produces mechanical and thermal damage 5 that culminates in a peri-implant "zone of death."…”
Section: Introductionmentioning
confidence: 99%